Good Corporate Governance System for Profit Management in Manufacturing Companies Listed BEI for 2020-2022 - Sutomo, Andi; Asrianto, Asrianto; Rais, Muh.; Karim, Abdul (Economics and Digital Business Review, 2024)
This research examines business governance's impact on the wage system. The independent changes used in this research are the board of commissioners, audit committee, and institutional authority. In this research, the size of the commission board is measured by including all commission board members in the company. The research committee in this study was evaluated based on the number of members of the company's book committee. In addition, the ownership structure of a company is estimated by the percentage of the number of shares owned by the entity from the number of residual components. Earnings management is presented as a type of cash-based option for Jones. This research used data from the Indonesian Stock Exchange (BEI). This research uses the example of the manufacturing sector listed on the Indonesia Stock Exchange for the 2020-2022 period. This research also shows that membership of the board of commissioners, audit committees, and institutions has a big influence on revenue management. However, only the Audit Committee influences revenue management.